2016
DOI: 10.22495/cocv13i3c3p6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental management accounting practices: major control issues

Abstract: The use of environmental management accounting (EMA) remains debated in South Africa and the literature reveals that EMA is still at an infancy stage in the emerging economies, including South Africa. Currently, there is limited existing research on environmental management accounting practices available for use by the hotel sector in South Africa. The overall aim of this study was to investigate and describe the use of the environmental management accounting tools by the hotel sector in the 3-5 star categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, Nyide and Lekhanya (2016) found that EMA adoption is not consistent across the board and not all hotels in South Africa have installed such systems to reduce major environmental costs. There is a lack of understanding on the factors influencing EMA adoption within the hotel companies.…”
Section: Ema Adoption In Hotel Industrymentioning
confidence: 99%
“…However, Nyide and Lekhanya (2016) found that EMA adoption is not consistent across the board and not all hotels in South Africa have installed such systems to reduce major environmental costs. There is a lack of understanding on the factors influencing EMA adoption within the hotel companies.…”
Section: Ema Adoption In Hotel Industrymentioning
confidence: 99%
“…Drivers for EMA implementations among others were: to adhere to government regulation and compliance (Chowdhury & Uddin, 2015;Le & Nguyen, 2019;Mohamad & Mohamed, 2018;Wachira & Wang'ombe, 2019). Other than that, cost reduction attempts were found to drive companies to implement EMA (Gunarathne & Lee, 2015;Marelli, 2015;Nyide & Lekhanya, 2016b;Wachira & Wang'ombe, 2019;Wahyuni et al, 2019). Apart from that, government-linked companies were seen to implement higher level of EMA implementation than their non-GLC counterparts (Huong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In another hotel-based research, Nyide and Lekhanya (2016b) revealed that cost reduction and leadership commitment were drivers for EMA implementation. Apart from that, strict environmental regulations and stakeholder pressures (such as guests) were among the drivers of EMA practices in the hotel.…”
Section: Ema Practices In Hospitality Industrymentioning
confidence: 99%
“…Stakeholders consistently pressure more ethical and responsible business conduct and demand corporations to develop an actionable plan for a greener and healthier environment (Nyide & Lekhanya, 2016). The pressure can arise from two types: formally by the legislative through written laws and regulations, and informally, such as the invention of norms, habits, and customs.…”
Section: Institutional Theorymentioning
confidence: 99%
“…Olalekan and Jumoke (2017) found this finding consistent with research that management barriers such as failure of the management in providing encouragement and leadership support as the factor hindering Nigerian companies from adopting EMAS. Furthermore, managers are often found to have little awareness of management practices related to the environment (Nyide & Lekhanya, 2016). Jalil, Abar, and Dadashian (2016) found that the obstacles to EMAS adoption are mainly due to the unwillingness of the companies to reveal their environmental information.…”
Section: Management Barriermentioning
confidence: 99%